Análisis de los costos de producción y rentabilidad del chifle de banano (Musa paradisiaca) y su incidencia en la economía familiar de las madres solteras del Cantón Mocache, Provincia de Los Ríos año 2014. - Loor Rocillo, Nancy Georgina (2015)
The research project "ANALYSIS OF THE COSTS OF PRODUCTION AND PROFITABILITY OF THE "chifle" OF BANANA (Musa paradisiaca) AND ITS INCIDENCE IN THE HOUSEHOLD ECONOMY OF THE ASSOCIATION OF SINGLE MOTHERS IN THE CANTON MOCACHE, PROVINCE OF THE RIVERS YEAR 2014" comes this initiative, because it is the palpable lack of employment, taking sometimes that work in the field doing forced labor, the single mothers in Canton. The market study showed a favorable acceptance for the marketing of the chifle banana, although 58% of the population has not consumed this appetizer but due to its high protein content and vitaminic qualify its flavor from excellent to good. The creation of the Microenterprise has an excellent reception by all the inhabitants of the canton, it is worth mentioning that the financing is going to be on the part of public institutions, such as GAD Mocache, GAD The Rivers and the Mies, taking an initial investment of 8,379.00 for the operation of the same; getting a sale of 800 covers daily daily "chifle" of bananas and a annual income from the sale of USD$96,000.00. The marketing strategy for the sale of chifles banana is addressed to students of 10 educational units prosecutors of the Canton, delivering 80 boots per day, it is worth mentioning that each institution has approximately 400 students. By what has been said above can say that the creation of the microenterprise Banachifle will improve the quality of life of single mothers of the Association "Women in Action" of the Canton Mocache.